Ibadah dan keadilan sosial: Interpretasi sosio-historis Amos 8:4-8 bagi hidup bergereja - Sipahutar, Roy Charly H. P. (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2021)
This paper is an attempt to explore the deepest message of Amos 8:4-8 with the socio-historical interpretation approach. Progress and prosperity that occurred in northern Israel in the 8th century BC gave birth to religious euphoria. The euphoria can be seen from the crowded places of worship visited by people to offer praise and sacrifice. But unfortunately, religious life has no impact at all on their social life, greed and oppression occur here and there. This is the background to the criticism of the prophet found in Amos 8: 4-8. The socio-historical interpretation approach used in this study is a tool to explore the meaning of the text by investigating the social context of the community when the text was written. The results of the interpretation explain that the middle and upper classes form an economic system that harms the lower classes, namely small farmers and urbanites. Worship is useless if it does not give rise to social care for others. Abstrak Tulisan ini adalah suatu upaya menggali pesan terdalam teks Amos 8:4-8. Kemajuan dan kemakmuran yang terjadi di Israel Utara pada abad 8 sM melahirkan euforia keagamaan. Euforia itu tampak dengan ramainya tempat-tempat peribadatan yang dikunjungi umat untuk menyampaikan pujian dan korban. Tetapi sayangnya kehidupan beragama tersebut tidak berdampak sama sekali bagi kehidupan sosial mereka, ketamakan serta penindasan terjadi di sana-sini. Hal inilah yang menjadi latar belakang kecaman nabi yang terdapat pada Amos 8:4-8. Interpretasi sosio-historis yang digunakan dalam penelitian ini adalah alat untuk menggali makna teks dengan menyelidiki konteks sosial masyarakat saat teks dituliskan. Hasil penafsiran menjelaskan bahwa kalangan menengah dan atas membentuk sistem perekonomian yang merugikan kalangan bawah yaitu petani kecil dan kaum urban. Ibadah menjadi sia-sia belaka bila tidak melahirkan sikap kepedulian sosial terhadap sesamanya.